Comprensiones de la Violencia Intrafamiliar en Quince Niños Y Niñas de 7 A 9 Años, Que Asisten A un Hogar de Apoyo Hagamos La Diferencia a Población En Situación de Vulnerabilidad de La Localidad Rafael Uribe Uribe De Bogotá (2016)
The present work of degree, it had as intention analyze the comprehensions that have of the violence intrafamiliar the children and girls from 7 to 9 years. To give fulfillment to this aim, a qualitative investigation appeared with a narrative design, using the interview and the participative workshops like technologies of compilation of information and the analysis of content like technology of analysis. The subjects of the sample were 15 minors of whom they represent to a home of support to population in situation of vulnerability of the locality Rafael Uribe Uribe of Bogotá. For the presentation of the results, it was considered to be the pictures of analysis, categorizing every story of the minors, maps of analysis and finally the analysis of the stories of the minors. The results showed that every minor has knowledge and approximation to the violence in the family, due to the exhibition there was analyzed that many of the minors are possessed by affective lacks and dynamic diffuse relatives who allow to demonstrate the needs of every minor as the lack of values and rules, there are no established roles and a bad administration of the authority is demonstrated.